The way to induce private participation in green finance and investment - Taghizadeh-Hesary, Farhad; Yoshino, Naoyuki (Finance research letters, 2019)
•Green credit guarantee scheme reduces risk of green finance.•Utilizing spillover effect of green energy increase rate of return of green projects.•Distributed ledger technologies increase the transparency in green finance.•Green finance is directly and indirectly related to various SDGs.•The paper is proposing two applied frameworks on green finance and investment. Establishment of green credit guarantee schemes (GCGSs) and returning a portion of the tax revenue originally generated from spillover effect of green energy supply to investors. It can reduce the risk of green finance and increase the rate of return of green energy projects, respectively. In addition, technical developments in the sphere of distributed ledger technologies provide the opportunity to increase the transparency in green finance and investments. This paper contributes to literature by proposing two applied frameworks, backed by theoretical models on green finance and investment based on projects size. The objective is to induce the private participation in green finance and investment.